QoS Routing in Telecommunications Networks - N. I. Listopad; O. A. Lavshuk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2022)
With the increasing demand for quality of service (QoS) in today's multiservice networks, more and more attention is paid to the routing facilities. With the transition to new generation networks, the issues of improving routing algorithms and protocols seem to be especially relevant. The existing routing algorithms have been developed quite fully and, on the whole, function effectively if the optimization of the route selection is carried out according to one parameter. In the case of multi-criteria routing, specialists are faced with the problem of reducing many criteria to a single one by means of additive convolution. Less commonly, multiplicative convolution is used, since it is not always possible to apply multiplicative transformation to real physical processes. The problem of applying multiplicative convolution to various QoS requirements is to choose the weight coefficients for each of the parameters. In this paper, we analyze the choice of the optimal path for multicriteria routing, taking into account the weight coefficients and cost parameters on the basis of the above twolevel approach. The results of numerical modeling of the search for the optimal path for various values of weight coefficients and cost coefficients are presented. It is shown that when choosing a path for multi-criteria optimization, it is necessary to choose the coefficients of the additive convolution as the product of the weight coefficients and the cost coefficients directly. It has been found that the value of the probability of packet transmission affects to a greater extent the choice of the optimal path than the values of the coefficients for the parameters of delay, delay variation, and bandwidth.